Influence of full range of motion vs. equalized partial range of motion training on muscle architecture and mechanical properties - Valamatos, Maria João; Tavares, Francisco; Santos, Rute M.; Veloso, António P.; Mil-Homens, Pedro (European journal of applied physiology, 2018)
Purpose The purpose of this study was to determine the effect of a 15-week partial range of motion (ROM) resistance training program on the vastus lateralis (VL) architecture and mechanical properties, when the time under tension (TUT) was equalized. Methods Nineteen untrained male subjects were randomly assigned to a control (Control; n = 8) or training (TG; n = 11) group. In the TG, the dominant and nondominant legs were randomly selected to be trained with a full ROM (FULL) or a partial ROM (PART) in an isokinetic dynamometer. Training volume was equalized based on the TUT by manipulating sets and repetitions. The VL muscle architecture was assessed by B-mode ultrasonography at rest and during maximal isometric knee extension contractions (MVCs) at ten knee angles. The VL fascicle force and specific tension were calculated from the MVCs with superimposed stimuli, accounting for the moment arm length, muscle architecture, and antagonist coactivation. Results The FULL training induced changes in fascicle length (FL) (4.9 ± 2.0%, P < 0.001) and specific tension (25.8 ± 18.7%, P < 0.001). There was a moderate effect of PART training on the physiological cross-sectional area (PCSA) (7.8 ± 4.0%, P < 0.001, d av = 0.6) and torque–angle adaptations (average increase 17.7 ± 3.9%, P < 0.05). Conclusions These results provide evidence that crucial architectural and mechanical muscle adaptations are dependent on the ROM used in strength training. It seems that muscle FL and specific tension can be increased by pure concentric training if greater ROM is used. Conversely, restricting the ROM to shorter muscle lengths promotes a greater PCSA and angle-specific strength adaptations.